Ophiolite-related associations of platinum-group minerals at Rudnaya, western Sayans and Miass, southern Urals, Russia. (18th April 2018) - Barkov, Andrei Y.; Tolstykh, Nadezhda D.; Shvedov, Gennadiy I.; Martin, Robert F.
ABSTRACT: We describe similar assemblages of minerals found in two placers in Russia, both probably derived from an ophiolitic source. The first is located along the River Rudnaya in the western Sayan province, Krasnoyarskiy kray, and the second pertains to the Miass placer zone, Chelyabinsk oblast, in the southern Urals. The platinum-group element (PGE) mineralization in both cases is mostly (at least 80%) represented by alloy minerals in the system Ru–Os–Ir, in the order of occurrence osmium, ruthenium and iridium. The remainder consists of Pt–Fe alloys and species of PGE sulfides, arsenides, sulfarsenides, etc. The associated olivine and amphiboles are supermagnesian, and the chromian spinel has a high Cr# value. The observed enrichment in Ru, typical of an ophiolitic source, may be due to high-temperature hydrothermal equilibration and mobilization in the ophiolite, as is the enrichment in Mg and Cr. Low-temperature replacement of the alloys led to the development of laurite, sulfoarsenides and arsenides. Some placer grains in both suites reveal unusual phases of sulfo-arsenoantimonides of Ir–Rh, e.g. the unnamed species (Rh, Ir)SbS and (Cu, Ni)1+ x (Ir, Rh)1– x Sb, where x = 0.2, and rhodian tolovkite, (Ir, Rh)SbS. Two series of natural solid-solutions appear to occur in the tolovkite-type phases. Among the oddities in the Rudnaya suite are globules of micrometric PGE sulfides, crystallites of platinum-group minerals, amphibole, and chalcopyrite bearing skeletal micrometric monosulfide-like compounds (Cu, Pt, Rh)S and (Pd, Cu)S1– x . Pockets of fluxed evolved melt seem to have persisted well below the solidus of the host Pt3 Fe-type alloy.